The Role of the Face Itself in the Face Effect: Sensitivity, Expressiveness, and Anticipated Feedback in Individual Compliance - Liu, Maggie Wenjing; Zhu, Qichao; Yuan, Yige (Frontiers in Psychology, 2019)
Face-to-face interactions are central to many individual choices and decision making issues, such as customer service, sales, promotions, and negotiations. While the face effect, i.e., face-to-face interactions are more effective in inducing compliance than other forms of interactions, has been noted in literature, its mechanism has rarely been explored. This research helps to fill the theoretical void and provides new insights into the face effect with two lab experiments and one field experiment. Study 1, a field experiment conducted in a beauty salon, and Study 2, a lab experiment, show that the face effect is largely attributable to anticipated facial feedback, and that the face effect is stronger when individuals are sensitive to face and when the requester’s face is expressive. Study 3 using video-simulated face-to-face interactions demonstrates that anticipated facial feedback, not necessarily actual feedback, is enough to drive the face effect. In so doing, this research furthers our understanding of factors that affect individual compliance in face-to-face interactions in both the “sending” and “receiving” stages. We discuss the theoretical and empirical implications, limitations, and future avenues of research.